DSP- and FPGA-Based Stair-Climbing Robot Design. (8th December 2013) - Wang, Ming-Shyan; Mi, Che-Min; Wu, Shih-Yu; Tu, Yi-Ming
Abstract : A stair-climbing robot is equipped with a grasping arm for capturing objects to provide service for the elders. A board based on a digital signal processor (DSP) plays the role of control center to manage all actions of two brushless DC motors for locomotion, two worm gears for torque magnification, and two DC motors for arms' pitching in the main body. The robot is steered by fuzzy logic control (FLC) which integrates the outputs of DC bus current sensor and an inclinometer. There is a CMOS camera for vision used in the robot, and the grasping arm is controlled via the video camera for capturing objects. Simple algorithms of image processing are implemented in the field programmable gate array (FPGA) board that generates the X -axis and Y -axis commands of the grasping arm to capture/load objects. Three walking experiments of the stair-climbing robot to move up and down stairs are shown in the taped pictures from videos. The object tracking and capturing by the grasping arm and camera verifies the proposed design.